The Relationship Need For Reading With Motivated Reading Citizens Package C at Pkbm Widya Dharma Nagari Solok Selatan - Ivany Nabila; Vevi Sunarti (Universitas Negeri Padang, 2020)
The background of this research is that the lack of interest in reading the citizens of learning package C at PKBM Widya Dharma Nagari Solok Selatan, researchers suspect the cause of this lack of interest in reading is a lack of need for reading. This study aims to describe the reading needs of learning citizens, to find out a description of the reading interests of learning citizens and how the relationship between the two. The type of this research is a quantitative study with a correlational approach. The population of this study was all citizens who studied package C who were active in PKBM Widya Dharma Nagari Solok Selatan during the 2019 school year, totaling 30 people. The sample in this study was taken as much as 65% with a total of 20 people. The data collection technique is in the form of a questionnaire with the data collection tool in the form of a questionnaire. The data analysis technique in this study used a percentage formula and Rank order. The results of this study indicate that: (1) the reading needs of learning citizens are still low, (2) the reading interest of learning citizens is still low, and (3) there is a significant relationship between reading needs and reading interest in learning package C in PKBM Widya Dharma Nagari Solok Selatan.Keywords: need for reading, interest in reading, learning citizen